Low frequency (74 MHz) radio continuum observations of the inner 13° × 7° of the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Rickert, M.; Yusef-Zadeh, F.; Brogan, C.
Abstract: We analyze a high resolution (114″ × 60″) 74 MHz image of the Galactic center taken with the Very Large Array (VLA). We have identified several absorption and emission features in this region, and we discuss preliminary results of two Galactic center sources: the Sgr D complex (G1.1–0.1) and the Galactic center lobe (GCL). The 74 MHz image displays the thermal and nonthermal components of Sgr D and we argue the Sgr D supernova remnant (SNR) is consistent with an interaction with a nearby molecular cloud and the location of the Sgr D Hii region on the near side of the Galactic center. The image also suggests that the emission from the eastern side of the GCL contains a mixture of both thermal and nonthermal sources, whereas the western side is primarily thermal.